2012
DOI: 10.1016/s1473-3099(11)70210-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of interferon-γ release assays for incident active tuberculosis: a systematic review and meta-analysis

Abstract: Special Programme for Research and Training in Tropical Diseases (WHO), Wellcome Trust, Canadian Institutes of Health Research, UK Medical Research Council, and the European and Developing Countries Clinical Trials Partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
339
5
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(379 citation statements)
references
References 55 publications
17
339
5
9
Order By: Relevance
“…However, this value needs to be taken with caution, given the uncertainties discussed here, and the lower rates reported in some other studies e.g. 19,20 .…”
Section: Authors' Contributionsmentioning
confidence: 63%
“…However, this value needs to be taken with caution, given the uncertainties discussed here, and the lower rates reported in some other studies e.g. 19,20 .…”
Section: Authors' Contributionsmentioning
confidence: 63%
“…In this regard, positive results of IGRA do not confirm diagnosis of acute TB infection. Thus, the gold standard diagnosis is still the detection of Mycobacterium tuberculosis by culture or PCR using infected samples [8,15]. In the present case, both patients were negative for tuberculin skin tests, while IGRA was positive, suggesting that the attending physicians consider the possibility of active TB as the potential cause of the fever of unknown origin, although a positive result with IGRA does not confirm the presence of active TB.…”
Section: Discussionmentioning
confidence: 56%
“…Fluorine-18-deoxyglucose-positron emission tomography/computed tomography (FDG-PET/ CT) has been used as a useful diagnostic tool in the detection of malignancy, inflammatory diseases and infectious diseases including TB [7]. In addition, interferongamma-releasing assay (IGRA) has emerged as a useful detection assay for active and latent TB, with higher sensitivity compared with the conventional diagnostic modalities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, before assuming the diagnosis of latent TB infection with all consequent public health actions, any QFT-IT positive result from newborn/infant should be accompanied either by a concomitant validated assay such as TST or by proof of absence of contaminating maternal cells/maternal antigenic material and of other IFN-gamma producing cells. Studies on these aspects, as well as on the true predictive value for TB of the available diagnostic tools (which are uniquely based on host immune response without evidence for pathogen activity 7 ) should be strongly encouraged and implemented by public health authorities. This would greatly help avoid uncertainties on data interpretations regarding both diagnosis of latent infection and actual risk of developing TB.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in a recent meta-analysis conducted on studies enrolling 26 680 participants, which also included children, demonstrated that in seven out of eleven studies the positivity of interferon-gamma released assays was lower than TST positivity. 7 Thus, based on the above considerations, the diagnosis of LTBI in newborns and infants who tested positive for QTF-IT and negative for TST would be neither warranted nor justified, and may derive from pitfalls and unperceived sources of error associated with the use of an indirect diagnostic technique in this age setting. The use of QFT-IT for the diagnosis of latent TB infection in newborns/infants necessarily implies that interferon-gamma (IFN-gamma) production by peripheral blood mononuclear cells (PBMCs) revealed by the QTF-IT is generated by MTB antigenspecific CD4z or CD8z T cells of infants.…”
Section: Discussionmentioning
confidence: 99%